Integration of Biological Networks for Acidithiobacillus thiooxidans Describes a Modular Gene Regulatory Organization of Bioleaching Pathways - Cortés, María Paz; Acuña, Vicente; Travisany, Dante; Siegel, Anne; Maass, Alejandro; Latorre, Mauricio (Frontiers in Molecular Biosciences, 2020)
Acidithiobacillus thiooxidans is one of the most studied biomining species, highlighting its ability to oxidize reduced inorganic sulfur compounds, coupled with its elevated capacity to live under an elevated concentration of heavy metals. In this work, using an in silico semi-automatic genome scale approach, two biological networks for A. thiooxidans Licanantay were generated: (i) An affinity transcriptional regulatory network composed of 42 regulatory family genes and 1,501 operons (57% genome coverage) linked through 2,646 putative DNA binding sites (arcs), (ii) A metabolic network reconstruction made of 523 genes and 1,203 reactions (22 pathways related to biomining processes). Through the identification of confident connections between both networks (V-shapes), it was possible to identify a sub-network of transcriptional factor (34 regulators) regulating genes (61 operons) encoding for proteins involved in biomining-related pathways. Network analysis suggested that transcriptional regulation of biomining genes is organized into different modules. The topological parameters showed a high hierarchical organization by levels inside this network (14 layers), highlighting transcription factors CysB, LysR, and IHF as complex modules with high degree and number of controlled pathways. In addition, it was possible to identify transcription factor modules named primary regulators (not controlled by other regulators in the sub-network). Inside this group, CysB was the main module involved in gene regulation of several bioleaching processes. In particular, metabolic processes related to energy metabolism (such as sulfur metabolism) showed a complex integrated regulation, where different primary regulators controlled several genes. In contrast, pathways involved in iron homeostasis and oxidative stress damage are mainly regulated by unique primary regulators, conferring Licanantay an efficient, and specific metal resistance response. This work shows new evidence in terms of transcriptional regulation at a systems level and broadens the study of bioleaching in A. thiooxidans species.